Actigraphy for quantitative evaluation of health - Denis G. Gubin; Alexander A. Markov; Svetlana V. Solovieva; Elena B. Khramova; Olga A. Malyugina; Yulianna A. Petrova; Julia V. Boldyreva (Russian Open Medical Journal, 2025)
An analysis of large-scale studies utilizing actigraphy and wearable devices for continuous monitoring of physiological measures was conducted. Data had been obtained from the UK Biobank and the National Health and Nutrition Examination Survey (NHANES) for use in the studies. The link between circadian rhythm deviations and health status was investigated. The amplitude and phase of circadian rhythms, along with variability parameters of physical activity, skin temperature, and light exposure, were found to be informative markers of key health indicators, including morbidity, mortality, and life expectancy. These findings highlight the critical role of circadian markers – amplitude, phase, and variability – in predicting health risks related to metabolic and sleep disorders, emotional well-being, and cognitive function. By exploring nonlinear associations between chronotype and health risks, we propose that personalized adjustment of sleep-wake phase, based on light hygiene and physical activity regimes and taking into account age, sex, and genetic cofactors, may contribute to the advancement of health-preserving technologies and the extension of human lifespan.